Applicability of trophic status indicators to Colorado Plains reservoirs - Stednick, John D., author; Hall, Emile B., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2003)
The recent proposed change in Cherry Creek Reservoir TMDL brought to light several issues about using a trophic status index (TSI) for water quality in Colorado reservoirs. Concerns range from applicability to interpretation. Off channel storage reservoirs along the South Platte River downstream of Denver, Colorado are often filled with river water that may contain high concentrations of nitrogen and phosphorous. This study measured reservoir nutrient concentrations from April through October 2001 in Jackson, Prewitt and North Sterling Reservoirs. Median total nitrogen (TN) concentrations were as follows: Jackson (2,550 mg/L), Prewitt (3,100 mg/L) and North Sterling (3,550 mg/L). Median total phosphorous (TP) concentrations were as follows: Jackson (208 mg/L), Prewitt (267 mg/L) and North Sterling (183 mg/L). An analysis of the applicability of common Trophic Status Index (TSI) models suggested that all reservoirs are eutrophic - hypereutrophic based upon chlorophyll-a, TP and Secchi depth measurements. Models using chlorophyll-a generally resulted in a lower trophic designation than those based upon TP. Model precision analysis (correlation coefficients, 95% confidence intervals, and average and percentage error) was used to evaluate 24 common models that predict chlorophyll-a from nutrient concentrations. Using precision analysis, models based upon TP were the best at Prewitt Reservoir, while models using TN and TP were best at Jackson and Sterling Reservoirs. This study suggested that one model does not fit all reservoirs. Based on precision analysis and model selection methods, nitrogen and phosphorous concentrations should be used when assessing off channel storage reservoir trophic status.
Keywords: Eutrophication -- Colorado -- Statistics; Water quality -- Colorado -- Measurement -- Statistics